Impact of Nrf2 on tumour growth and drug sensitivity in oncogenic K-ras-transformed cells in vitro and in vivo. (3rd June 2018) - Shao, Jiajia; Glorieux, Christophe; Liao, Jianwei; Chen, Ping; Lu, Wenhua; Liang, Zhenhao; Wen, Shijun; Hu, Yumin; Huang, Peng
Abstract: K-ras is one of the most common oncogenes in human cancers, and its aberrant activation may lead to malignant transformation associated with oxidative stress and activation of the transcription factor Nrf2 that regulates multiple detoxification enzymes. The purpose of this research was to use gene editing technology to evaluate the role of Nrf2 in affecting tumour growth and drug sensitivity of K-ras G12V -transformed cells. We showed that induction of K-ras G12V caused a significant activation of Nrf2 associated with increased expression of its target genes NAD(P)H:quinone oxidoreductase 1 (NQO1) and haem oxygenase-1 (HO-1). Interestingly, knock-out of Nrf2 by CRISPR/Cas9 in K-ras G12V -expressing cells only impacted the expression of NQO1 but not HO-1. We also found that Nrf2 knock-out caused high reactive oxygen species (ROS) stress, suppression of cell proliferation, increased apoptosis in vitro, and a decrease of tumour growth in vivo . Furthermore, abrogation of Nrf2 significantly increased the sensitivity of K-ras G12V cells to multiple anticancer agents including phenethyl isothiocyanate (PEITC), doxorubicin, etoposide, and cisplatin. These results show that genetic abrogation of Nrf2 impairs the malignant phenotype of K-Ras G12V -transformed cells in vitro and in vivo, and demonstrates the critical role of Nrf2 in promoting cell survival and drug resistance in cells harbouring oncogenic K-ras. As such, inhibition of Nrf2 would be an attractive strategy to increase the therapeutic effect and overcome drug resistance in cancer with oncogenic K-ras activation.